2011
DOI: 10.1186/1475-925x-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Formant analysis in dysphonic patients and automatic Arabic digit speech recognition

Abstract: Background and objectiveThere has been a growing interest in objective assessment of speech in dysphonic patients for the classification of the type and severity of voice pathologies using automatic speech recognition (ASR). The aim of this work was to study the accuracy of the conventional ASR system (with Mel frequency cepstral coefficients (MFCCs) based front end and hidden Markov model (HMM) based back end) in recognizing the speech characteristics of people with pathological voice.Materials and methodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…It may be inferred from these findings that compared to individuals without voice quality deviation, patients with a mild to moderate degree of deviation may implement supraglottic adjustments to compensate for dysfunctional glottic conditions with the presence of increased silent airflow. These findings are consistent with other studies (8)(9)(10)(13)(14)(15) showing that dysphonic patients tend to make adjustments in the vocal tract to compensate for their voice problem.…”
Section: Traditional Acoustic and Formantic Measures In The Discriminsupporting
confidence: 93%
See 1 more Smart Citation
“…It may be inferred from these findings that compared to individuals without voice quality deviation, patients with a mild to moderate degree of deviation may implement supraglottic adjustments to compensate for dysfunctional glottic conditions with the presence of increased silent airflow. These findings are consistent with other studies (8)(9)(10)(13)(14)(15) showing that dysphonic patients tend to make adjustments in the vocal tract to compensate for their voice problem.…”
Section: Traditional Acoustic and Formantic Measures In The Discriminsupporting
confidence: 93%
“…Some studies (8)(9)(10)(13)(14)(15) have observed that patients with a voice disorder make adjustments not just in the glottis but also in the supraglottis. These patients have lower formant values (F1, F2, F3) than individuals without a voice disorder (10,13,15) .…”
Section: Introductionmentioning
confidence: 99%
“…For speech feature extraction, we extracted 65 features from the collected data set. The extracted features consisted of pitch, average ratio of pitch period, correlation coefficient between F0 and intensity (CORR), absolute Jitter (Jita), and Mel frequency cepstral coefficients (MFCC), among others [18, 23, 27]. The specific content of the extracted features is described in Table 1, and sample of speech signal recording of 5 vowels and one sentence is showed in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…20 It was found that the learning of vector quantization methodology performed better than the multilayer perceptron architecture in voice pathology detection with the sustained vowel jɑj. ASR system for Arabic words with various dysphonic patients was studied by Muhammad et al 21 They reported that speech samples from sulcus vocalis patients were recognized the least (56%), whereas that from patients with vocal fold nodules were better recognized (84.5%). Wavelet decomposition and neural network-based voice pathology detection were proposed by Salhi et al 22 Energy from different subbands of wavelet was used as features.…”
Section: Etcmentioning
confidence: 99%